Tinjauan Kritis Pendekatan Komunikatif Dalam Pembelajaran Bahasa Arab di Era Digital - Rizqi Mauliddiyah; Sheila Salsabilla; Ahmad Nur Mizan (Advances In Education Journal, 2026)
This study examines the implementation of the communicative approach in Arabic language learning in the digital era. The communicative approach emphasizes the use of language as a tool for active and contextual communication. This research aims to analyze the advantages, weaknesses, and development solutions of digital based communicative learning in Arabic education. The study uses a qualitative method with a library research design by collecting data from relevant journals, books, and scientific articles. The findings show that the communicative approach improves students’ language skills, increases self confidence, enhances learning motivation, and creates a more interactive and collaborative learning environment. However, several challenges remain, such as unequal student participation, limited teacher competence in managing technology-based communicative learning, and inadequate facilities and internet access. Therefore, appropriate technology integration and the adjustment of learning strategies to students’ characteristics and needs are essential to support effective, innovative, and sustainable Arabic language learning in the digital era